Antennal transcriptomic analysis of carboxylesterases and glutathione S-transferases associated with odorant degradation in the tea gray geometrid, Ectropis grisescens (Lepidoptera, Geometridae) - Zhang, Fangmei; Chen, Yijun; Zhao, Xiaocen; Guo, Shibao; Hong, Feng; Zhi, Yanan; Zhang, Li; Zhou, Zhou; Zhang, Yunhui; Zhou, Xuguo; Li, Xiangrui (Frontiers in Physiology, 2023)
Carboxylesterases (CXEs) and glutathione S-transferases (GSTs) can terminate olfactory signals during chemosensation by rapid degradation of odorants in the vicinity of receptors. The tea grey geometrid, Ectropis grisescens (Lepidoptera, Geometridae), one of the most devastating insect herbivores of tea plants in China, relies heavily on plant volatiles to locate the host plants as well as the oviposition sites. To better understand the genes involved in signal termination and odorant clearance in this major tea pest, we 1) constructed and sequenced antennal transcriptomes from adult males and females, 2) identified and cloned CXEs and GSTs, and finally 3) compared spatial expression profiles of these genes in both sexes. As a result, we identified 28 CXEs and 16 GSTs from female and male antennal transcriptomes. Phylogenetic analyses clustered these candidates into several clades, among which antennal CXEs, mitochondrial and cytosolic CXEs, and delta group GSTs contained genes commonly associated with odorants degradation. Spatial expression profiles showed that most CXEs (26) were expressed in antennae. In comparison, putative GSTs exhibited a diverse expression pattern across different tissues, with one GST expressed specifically in the male antennae. These combined results suggest that 12 CXEs (EgriCXE1, 2, 4, 6, 8, 18, 20-22, 24, 26, and 29) and 5 GSTs (EgriGST1 and EgriGST delta group) provide a major source of candidate genes for odorants degradation in E. grisescens.